Preparation method of hollow Ti3C2-coated TiSe2 heterostructure and application of hollow Ti3C2-coated TiSe2 heterostructure in secondary battery
By constructing a heterostructure hollow Ti3C2@TiSe2 composite material and loading TiSe2 nanoparticles by in-situ selenization method, the problem of slow diffusion rate of sodium ions in sodium ion batteries is solved, and higher theoretical capacity and cycling performance are achieved, which improves the practical application prospects of sodium ion batteries.
Patent Information
- Application Number
- CN202311081990.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-26
- Publication Date
- 2025-02-28
AI Technical Summary
The diffusion rate of sodium ions in sodium ion batteries is slow and the reaction kinetics is insufficient, resulting in the limitation of the specific capacity and practical application prospects of the battery.
Heterostructured hollow Ti3C2@TiSe2 composite material is used as the negative electrode material for sodium ion batteries. By constructing a three-dimensional MXene spherical structure, one-dimensional TiSe2 nanoparticles are loaded, and TiSe2 nanoparticles are uniformly loaded by in-situ selenization method to improve the conductivity and cycling performance of the material.
Compared with traditional hard carbon negative electrode materials, the heterostructure hollow Ti3C2@TiSe2 composite material has a larger theoretical capacity and better cycling performance, which effectively alleviates the problem of ion volume expansion in electrochemical reactions and improves capacity and rate performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the material preparation of secondary battery negative electrode materials, and in particular to the technical field of improving the circulation and rate performance of transition metal selenides, sulfides, and heterostructure-related composite materials in secondary ion batteries. Background Art
[0002] At present, more and more people are beginning to realize the unsustainability of fossil energy, because the use of such energy has caused increasing carbon emissions and greenhouse effect problems. This has promoted the exploration of clean energy and the research of new energy storage technologies, but this is inevitably limited by its uneven geographical distribution and inability to provide continuous power supply. Among the energy storage methods, electrochemical energy storage is an indispensable part. As a strong competitor to lithium-ion batteries, sodium-ion batteries not only make up for the shortcomings of lithium resources, but also have the benefit of low cost. These advantages also make sodium-ion batteries considered to be a very promising alternative. But the challenging thing is that although sodium-ion batteries and lithium-ion batteries have similar reaction mechanisms and the same internal battery structure, the larger ionic radius of sodium ions (1.02 Å) relative to the radius of lithium ions (0.76 Å) leads to a slower diffusion rate of sodium ions in the battery and insufficient reaction kinetics. To address the above problems, we can study electrode materials with excellent performance to alleviate volume expansion and poor chemical kinetics, and further promote the specific capacity and practical application prospects of sodium-ion batteries. Past research has focused on carbon materials, including carbon spheres, carbon nanofibers, graphene and carbon nanotubes as negative electrode materials for sodium-ion batteries. These materials promote Na + Insertion and deinsertion, which promotes slow kinetics, improves electronic conductivity, and mitigates the significant expansion that may occur. However, the low specific capacity of hard carbon materials is insufficient for practical high energy density device applications. Graphene-like carbide Ti3C2 belongs to MXene, another branch of two-dimensional materials. The strong conductivity, controllable structure and huge surface area of MXene make it a versatile material for energy storage applications. However, in practical applications, the presence of interlayer van der Waals forces makes the material easy to stack, which seriously hinders electron transport and Na + In most cases, the general strategy to improve electrochemical performance is to build a heterostructure by combining MXene and other nanomaterials. Metal selenides are promising candidate materials for SIBs anodes due to their high theoretical capacity. However, the conductivity and volume expansion during the reaction process become a problem that cannot be ignored. These can be improved by building nanomaterials and heterostructures, which is the key to material design and the starting point of this patent. Summary of the invention
[0003] In view of the above-mentioned experimental design problems, the purpose of the present invention is to provide a heterogeneous structure hollow Ti3C2@TiSe2 composite material, which is composed of a three-dimensional MXene spherical structure loaded with one-dimensional TiSe2 nanoparticles. By constructing heterogeneous structure materials of different dimensions and using them for the negative electrode of sodium ion batteries, an in-situ selenization strategy is used in the synthesis process to make TiSe2 nanoparticles uniformly loaded on the spherical MXene. Compared with traditional hard carbon negative electrode materials, the heterogeneous structure hollow Ti3C2@TiSe2 composite material has a larger theoretical capacity and better cycle performance. The key features of the material synthesized by this method are: a simple template method and solid phase sintering method are used to obtain Ti3C2@TiSe2 by in-situ selenization; titanium selenide with high conductivity grows uniformly on the surface of the spherical MXene layer. This unique structure makes up for the lack of structural stability of MXene and shortens the electron diffusion distance during the electrochemical reaction; improves the conductivity of the material, and the composite of MXene and TiSe2 structure can effectively alleviate the problem of ion volume expansion during the electrochemical reaction, and further improve its capacity and rate performance.
[0004] To achieve the above-mentioned purpose, the specific technical invention scheme of the present invention is a method for preparing a heterogeneous structure hollow Ti3C2@TiSe2 composite material, the specific feature of which is that the hollow spherical MXene precursor increases the specific surface area, and the in-situ selenization also allows TiSe2 to be evenly loaded on the surface of the spherical MXene.
[0005] The preparation method comprises the following steps (1) Preparation of lamellar MXene: Slowly add an appropriate amount of Ti3AlC2 powder into HCl solution and stir for 30 min to make it dissolve evenly. After it is fully dissolved, slowly add a certain amount of LiF into the above solution and stir in an oil bath. Finally, centrifuge to obtain a black precipitate, and take the supernatant as the final lamellar MXene colloid; (2) Preparation of MXene@PMMA: An appropriate amount of MXene colloidal solution was mixed with a certain amount of PMMA solution and stirred thoroughly. Finally, the mixture was collected by centrifugation and washed with deionized water. The gray powder was dried in a vacuum drying oven overnight to obtain MXene@PMMA. (3) Preparation of Ti3C2@TiSe2: An appropriate amount of MXene@PMMA and a certain amount of selenium powder are placed in the upstream and downstream of the gas flow, respectively. The selenization and template removal processes are completed simultaneously under an argon atmosphere. After reaching the specified temperature, the temperature is kept constant and taken out after cooling to room temperature.
[0006] In the above preparation method, the concentration of HCl in step (1) is 0.1 mol L -1The mass ratio of LiF to Ti3AlC2 is about 1:2, the reaction time is 36-48 hours, the sample needs to be washed until the solution is neutral, and the reaction temperature is 25-30 ℃; In the above preparation method, the reaction time in step (1) is 36-48 hours; In the above preparation method, when washing the sample in step (1), the pH of the solution needs to be 6-7, and the reaction temperature is 45-55°C; In the above preparation method, the concentrations of the MXene colloid solution and the PMMA solution in step (2) are 10 g L -1 , 5 g L -1 , the volume ratio of MXene colloid solution and PMMA solution is 1:1; In the above preparation method, the reaction temperature in step (2) is 25-30°C, and the drying temperature is 60-70°C; In the above preparation method, the mass ratio of the two in step (3) is 1:2, and the heating rate is 5 °C min -1 , the specified temperature is 450 ℃ and the holding time is 3 hours.
[0007] The present invention provides a Ti3C2@TiSe2 composite heterostructure material suitable for use in sodium ion batteries and having excellent electrical conductivity and ion transfer rate. Compared with traditional sodium ion battery negative electrode materials, the present invention has the following advantages: (1) The two-dimensional lamellar structure is transformed into a three-dimensional spherical structure through the template method and its own electrostatic adsorption, which greatly increases the specific surface area of the base material and also exposes more active sites to a certain extent.
[0008] (2) During the selenization process, de-templating is completed at the same time, and finally a spherical structure of uniform size and hollow core is obtained. Small TiSe2 particles are added to the surface, which further improves the conductivity of the material, shortens the electron transmission distance, and promotes the embedding and extraction of sodium ions in the reaction.
[0009] (3) Ti3C2 obtained by carbonization of three-dimensional spherical MXene can strongly adsorb TiSe2 through chemical bonds. In the specific electrochemical reaction process, Ti3C2 can provide high conductivity, while TiSe2 and Na + The reaction generates Na x As an intermediate product of TiSe2 (x=0-1), the composite of heterogeneous materials not only improves the conductivity, but also provides a new direction for the actual commercial use of sodium-ion batteries.
[0010] Instruction Manual Figure 1: Schematic diagram of a preparation method of a heterostructure hollow Ti3C2@TiSe2 composite material; Figure 2 : Transmission electron microscopy (TEM) image of heterostructure hollow Ti3C2@TiSe2 composite material; Figure 3 : X-ray diffraction (XRD) pattern of heterostructure hollow Ti3C2@TiSe2 composite material; Figure 4 : Cycling performance diagram of heterostructure hollow Ti3C2@TiSe2 composite material assembled into a full battery with commercial Na3V2(PO4)3.
[0011] Specific implementation cases The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present application, rather than to limit the present application. Example 1
[0012] The preparation of the heterogeneous structure hollow Ti3C2@TiSe2 composite material includes the following steps: (1) Preparation of MXene flakes: Based on the basic principle of etching the Al layer in Ti3AlC2 by the reaction of LiF and HCl to generate HF, 2.0 g Ti3AlC2 powder was slowly added into a 0.1 mol L -1 HCl solution, stirred for 30 minutes to make it dissolve evenly. After it is fully dissolved, 3.2 g LiF is slowly added to the above solution. HF will be generated at this time. Then it is stirred in an oil bath and the temperature is maintained at 45 °C to promote the reaction between HF and the Al layer in Ti3AlC2 to fully peel it off. After stirring and reacting for 36 hours, since the single-layer MXene has a lower mass than the multi-layer MXene, the supernatant is taken as the final sheet MXene colloid during the centrifugation process. At the same time, in order to ensure that HF is fully removed during the centrifugation process, it is necessary to observe the pH of the solution during the centrifugation process until the pH of the solution is greater than 6, which can basically ensure the removal of HF. (2) Preparation of MXene@PMMA: 500 mg of PMMA powder was placed in 500 ml of deionized water, stirred thoroughly to dissolve it, and ultrasonicated for 30 minutes to evenly disperse it. After dissolution and dispersion, the electrostatic interaction between the rich negatively charged groups on the surface of MXene and the positively charged groups on the surface of PMMA was used to evenly coat the spherical PMMA with a few layers of MXene. The 2-fold diluted lamellar MXene colloid was added dropwise to the PMMA suspension, stirred thoroughly at room temperature for 24 hours, and finally collected by centrifugation and washed with deionized water to obtain a gray powder, which was placed in a vacuum drying oven overnight to obtain MXene@PMMA. (3) Preparation of Ti3C2@TiSe2: 2 g of MXene@PMMA and 4 g of selenium powder were placed in the upstream and downstream of a tube furnace equipped with an argon protective atmosphere, respectively. The PMMA de-templating process and in-situ selenization process were completed at high temperature. The temperature control program was set at 2 °C min -1 The belt was heated at a heating rate of 210 minutes. When it reached 450°C, it was kept at this temperature for 2 hours. To prevent oxidation during the high temperature process, it was taken out after naturally cooling to room temperature. Figure 2 It can be seen that it has an obvious hollow structure and uniform loading of TiSe2 on the surface, with a diameter of about 2 μm. Figure 3 It can also be seen from the XRD spectrum that it matches the TiSe2 standard card well. Example 2
[0013] (1) Preparation of accordion-shaped MXene: Based on the basic principle of etching the Al layer in Ti3AlC2 by the reaction of LiF and HCl to generate HF, 2.0 g Ti3AlC2 powder was slowly added into a 0.1 mol L -1 HCl solution, stirred for 30 minutes to make it dissolve evenly. After it is fully dissolved, 3.2 g LiF is slowly added to the above solution. HF will be generated at this time. Then it is stirred in an oil bath and the temperature is maintained at 45 °C to promote the reaction between HF and the Al layer in Ti3AlC2, so that it can be fully peeled off. After stirring and reacting for 12 hours, since the accordion-shaped MXene has a larger mass, the lower layer of precipitate is taken as the final product during the centrifugation process. At the same time, in order to ensure that HF is fully removed during the centrifugation process, it is necessary to observe the pH of the solution during the centrifugation process until the pH of the solution is greater than 6, which can basically ensure the removal of HF. After the centrifugation is completed, it is kept in a vacuum oven at 60 °C for 12 hours to obtain the accordion-shaped MXene; (2) Preparation of Ti3C2@TiSe2: 2 g of accordion-shaped MXene and 4 g of selenium powder were placed in the upstream and downstream of a tube furnace equipped with an argon protective atmosphere, respectively. The selenization process on the surface of the accordion-shaped MXene was completed at high temperature. The temperature control program was set at 2 °C min -1 The belt was heated at a heating rate of 210 minutes. When the belt reached 450°C, the temperature was maintained for 2 hours. To prevent oxidation during the high temperature process, the belt was taken out after naturally cooling to room temperature. Example 3
[0014] (1) Preparation of MXene flakes: Based on the basic principle of etching the Al layer in Ti3AlC2 by the reaction of LiF and HCl to generate HF, 2.0 g Ti3AlC2 powder was slowly added into a 0.1 mol L -1 HCl solution, stirred for 30 minutes to make it dissolve evenly. After it is fully dissolved, 3.2 g LiF is slowly added to the above solution. HF will be generated at this time. Then it is stirred in an oil bath and the temperature is maintained at 45 °C to promote the reaction between HF and the Al layer in Ti3AlC2 to fully peel it off. After stirring and reacting for 36 hours, since the single-layer MXene has a lower mass than the multi-layer MXene, the supernatant is taken as the final sheet MXene colloid during the centrifugation process. At the same time, in order to ensure that HF is fully removed during the centrifugation process, it is necessary to observe the pH of the solution during the centrifugation process until the pH of the solution is greater than 6, which can basically ensure the removal of HF. (2) Preparation of MXene@PMMA: 500 mg of PMMA powder was placed in 500 ml of deionized water, stirred thoroughly to dissolve it, and ultrasonicated for 30 minutes to evenly disperse it. After dissolution and dispersion, the electrostatic interaction between the rich negatively charged groups on the surface of MXene and the positively charged groups on the surface of PMMA was used to evenly coat the spherical PMMA with a few layers of MXene. The 2-fold diluted lamellar MXene colloid was added dropwise to the PMMA suspension, stirred thoroughly at room temperature for 24 hours, and finally collected by centrifugation and washed with deionized water to obtain a gray powder, which was placed in a vacuum drying oven overnight to obtain MXene@PMMA. (3) Preparation of Ti3C2@TiS2: 2 g of MXene@PMMA and 4 g of sulfur powder were placed in the upstream and downstream of a tube furnace equipped with an argon protective atmosphere, respectively. The PMMA de-templating process and in-situ sulfurization process were completed at high temperature. The temperature control program was set at 2 °C min -1 The belt was heated at a heating rate of 210 minutes. When the belt reached 450°C, the temperature was maintained for 2 hours. To prevent oxidation during the high temperature process, the belt was taken out after naturally cooling to room temperature.
Claims
1. The present invention provides a heterogeneous hollow Ti3C2@TiSe2 composite material, characterized in that MXene and TiSe2 were tightly combined together through in-situ growth to prepare Ti3C2@TiSe2 composite material as the negative electrode of sodium ion battery. In this unique structure, the in-situ generated TiSe2 is tightly bonded to the spherical MXene through chemical bonds, which also provides abundant active sites and can effectively shorten the distance of electron diffusion, further alleviating the volume expansion problem of sodium ions during the embedding and de-embedding process, and maintaining its structural stability during the electrochemical reaction.
2. The present invention provides a method for preparing a heterostructure hollow Ti3C2@TiSe2 composite material, comprising the following steps: (1) Preparation of lamellar MXene: Slowly add an appropriate amount of Ti3AlC2 powder into HCl solution and stir for 30 minutes to dissolve it evenly. After it is fully dissolved, slowly add a certain amount of LiF into the above solution and stir at a certain temperature. Finally, centrifuge to obtain a black precipitate and take the supernatant as lamellar MXene colloid. The concentration of HCl is 0.1 M, the mass ratio of LiF to Ti3AlC2 is about 1:2, and the sample needs to be washed until the solution is neutral. The reaction temperature is 25-30 °C. The reaction time is 36-48 hours. The solution pH is 6-7 and the reaction temperature is 45-55 °C. (2) Preparation of MXene@PMMA: Mix an appropriate amount of MXene colloid solution with a certain amount of PMMA solution and stir thoroughly. Finally, collect by centrifugation and wash with deionized water. Dry the gray powder in a vacuum drying oven overnight to obtain MXene@PMMA. The concentrations of MXene colloid solution and PMMA solution are 10 g L -1 , 5 g L -1 ; The volume ratio of MXene colloidal solution to PMMA solution is 1:1, the reaction temperature is 25-30 °C, and the drying temperature is 60-70 °C; (3) Preparation of Ti3C2@TiSe2: An appropriate amount of MXene@PMMA and a certain amount of selenium powder are placed in the upstream and downstream of the gas flow, respectively. The selenization and template removal processes are completed in an argon atmosphere. After reaching the specified temperature, the solution is kept warm and taken out after cooling to room temperature. The mass ratio of the two is 1:2, and the heating rate is 5 °C min -1 , the specified temperature is 450 ℃ and the holding time is 3 hours.